Determination of microscopical parameters of heterogeneous carbon materials - Dorosinets, Vladimir A.; Borisov, Victor A. (Journal of the Belarusian State University. Physics, 2019)
Experimental studies of the temperature dependence of the resistance and magnetoresistance of the composite metal-carbon samples C(Co), which show the effect of weak localization, have been carried out. The magnetoresistance at a temperature T = 2.2 K is alternating, which is explained by the spin-orbit interaction. Analysis of the magnetoresistance curves made it possible to calculate the values of the parameters characterizing the phase loss time in inelastic scattering and the spin-orbit interaction time. For the parameter characterizing the elastic scattering time, the minimum value was estimated.
Keywords: carbon; quantum correction; weak localization; magnetoresistance